Adsorção de sulfametoxazol usando carvão ativado produzido a partir de sementes de graviola (Annona muricata): modelagem e simulação - Santos, Washington Lima dos (2019)
The presence of pharmaceutical compounds in the environment is considered an emerging concern due to its harmful effects on exposed organisms, as well as the lack of specific legislation. Thus, alternative technologies for the detection and removal of contaminants from water have been developed. In this work, it is proposed to estimate parameters of the adsorption process of sulfametozaxol (SMX) in activated carbon (CA) produced from graviola (Annona muricata) seeds. Batch adsorption assays provided data for the study of equilibrium and adsorption kinetics. In the proposed model, the estimated parameters were the diffusion coefficient of the component (Def), the mass transfer coefficient (ke), the maximum adsorption capacity (qm) and the desorption equilibrium constant (Kd). The mathematical model was solved using the line method in the discretization of partial differential equations. The DASSL subroutine was used to integrate the system of differential equations resulting from the application of the line method and the parameters were estimated through the ESTIMA program, associated with the Particle Swarm (PSO) algorithm. The results found for the best fit to the model provided the following values for the parameters: qm = 44,76 mg mL−1 , Kd = 9,98 ∙ 10−4 mg mL−1 ,Def = 1,00 ∙ 10−11 m2 s −1 e Ke = 4,29 ∙ 10−4 m s −1 . The CA was characterized using the following techniques: Surface Area Analysis (BET) and Porosity Size Distribution (BJH), X-Ray Fluorescence (FRX) and Scanning Electron Microscopy (SEM). The comparison of the equilibrium and kinetic data obtained experimentally with the simulated curves showed that the proposed model is suitable for the study of this system. Finally, simulations were performed to evaluate the effect of the parameters Def and Ke on the adsorption kinetics of SMX.